Replacing adenoviral vector HVR1 with a malaria B cell epitope improves immunogenicity and circumvents preexisting immunity to adenovirus in mice - Shiratsuchi, Takayuki; Rai, Urvashi; Krause, Anja; Worgall, Stefan; Tsuji, Moriya (The Journal of Clinical Investigation, 2010)
Although adenovirus (Ad) has been regarded as an excellent vaccine vector, there are 2 major drawbacks to using this platform: (a) Ad-based vaccines induce a relatively weak humoral response against encoded transgenes, and (b) preexisting immunity to Ad is highly prevalent among the general population. To overcome these obstacles, we constructed an Ad-based malaria vaccine by inserting a B cell epitope derived from a Plasmodium yoelii circumsporozoite (CS) protein (referred to as the PyCS-B epitope) into the capsid proteins of WT/CS-GFP, a recombinant Ad expressing P. yoelii CS protein and GFP as its transgene. Multiple vaccinations with the capsid-modified Ad induced a substantially increased level of protection against subsequent malaria challenge in mice when compared with that of unmodified WT/CS-GFP. Increased protection correlated with augmented antibody responses against the PyCS-B epitope expressed in the capsid. Furthermore, replacement of hypervariable region 1 (HVR1) of the Ad capsid proteins with the PyCS-B epitope circumvented neutralization of the modified Ad by preexisting Ad-specific antibody, both in vivo and in vitro. Importantly, the immunogenicity of the Ad-containing PyCS-B epitope in the HVR1 and a P. yoelii CS transgene was maintained. Overall, this study demonstrates that the HVR1-modifed Ad vastly improves upon Ad as a promising malaria vaccine platform candidate.